STRENGTHS, WEAKNESSES, OPPORTUNITIES AND THREATS (SWOT) ANALYSIS OF THE NIGERIA AGRICULTURAL TRANSFORMATION AGENDA (ATA) (2014)
Agricultural Transformation (AT) requires a new and different approach to policy making and implementation. It entails search by government for greater integration and co-ordination, looks for an approach that is characterized by greater partnership between federal, state and local government, economic entities, private industry and other community groups. The process involves diversification in the sector to meet changing domestic and trade demands. This study was mainly contents review of relevant literature and use of situation analysis. We examined agricultural policies changes in Nigeria and draw some lessons from successful agriculturally transformed countries. The results show that, bypassing small farmers during the process of AT is capable of marginalizing a large group of the rural population and cause social tensions. AT requires a comprehensive long term strategy that needs to be supported by long term commitment from the government and international development partners. The various steps Nigeria had taken in its AT process are necessary but not sufficient conditions for a successful transformation. Successful AT must be broad-based with efficient infrastructural investments in roads network, irrigation, consistent energy supply, high-speed and affordable communications, clear and consistent long-term policies, good working relationship among ministries and governmental bodies, effective rule of law, and good adaptation and mitigation measures consistent with sustainable development.